Aplicação de modelos matemáticos ao amadurecimento de tomates recobertas por blendas de polissacarídeos durante o armazenamento - Lima, Fernanda Freire (Universidade Federal Rural do Semi-Árido, 2018)
Intensive use of non-renewable plastic materials causes environmental problems. Biopolymer materials that are non-toxic and biodegradable can partially replace plastic in many applications. Biopolymers based on polysaccharides have been analyzed as coatings for application in fruits with the objective of extending their useful life without harming the environment.Tomato is a fruit of high world consumption, which is highly perishable, because it is climacteric. In this work, pure and mixed coatings of chitosan, cassava starch and tamarind xyloglucan were applied to tomatoes at concentrations of 0.75%, 1.5% and 3.0% of dry mass ofbiopolymer, and their effects on mass loss and total colour variation in treated fruits were evaluated. The mass loss was described by linear mathematical models. The total colour variation was described bynon-linear mathematical models: Gompertz, Bertallanfy, logistic and Brody. The parameters obtained for the models were estimated by regression by least squares method. Among 21 treatments analysed, the 3 treatments that presented more significant effects in the color were chosen to be evaluated about their influence on the maturing of the tomatoes. The sessile drop method was used to confirm the hydrophilicity of the coatings by measuring the contact angle and the surface of the coated tomatoes was observed using optical microscopy.Analysis of firmness, acidity, soluble solids and pigments (chlorophyll A and B, lycopene and β-carotene) were also performed. It was observed that the lowest rates of mass loss were observed in the coated tomatoes at the concentration of 3.0% dry mass, with the binary chitosan and manioc starch mixture (1: 1) being the composition that caused a larger reduction in rate of mass loss at this concentration. The logistic model best described the evolution of color in tomatoes covered with 0.75% and 1.5% coverage, while the Gompertz model best described the color evolution for the concentration of 3.0%. By the values of the parameters of the estimated models A and k, it can be inferred that the maturation occurred more slowly in the fruits submitted to the mixtures T2 (starch), T3 (xyloglucan) and T7 (chitosan + starch + xyloglucan). 3.0% of dry mass underwent anaerobiosis, and T3 (xyloglucan) presented high rates of mass loss. Thus, T1 (chitosan), T2 (starch) and T4 (chitosan + starch) in the concentration of 1.5% of dry mass were the treatments chosen for the physical-chemical analysis of the fruits. The analysis of the contact angles showed that the biopolymer coatings are hydrophilic, and the cassava starch (T2) coating had the lowest contact angle. By optical microscopy, it was possible to see that the coverage of chitosan binary composition and cassava starch (1: 1) provided a greater barrier to gas exchange when compared to other coverages. No influencesof the applied coatings were observed on the firmness of the tomatoes, nor on the variation of soluble solids content and chlorophyll A concentration. The chitosan treatment showed a greater influence on the titratable acidity variation as well as on the concentration of lycopene and β-carotene. The treatment with chitosan + starch (1: 1) showed greater influence on the variation of the TSS / AT ratio and the variation of the concentration of chlorophyll B
Keywords: Cobertura; Biopolímero; Polissacarídeo; Tomate; Modelos matemáticos não lineares; Coatings; Biopolymer; Polysaccharide; Tomato; Non linear mathematical models; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA